Precarious employment and migrant workers’ mental health: a protocol for a systematic review of observational studies - Ozlem Koseoglu Ornek; Tobias Weinmann; Julia Waibel; Katja Radon (Systematic Reviews, 2020)
Abstract Background Precarious employment has become an urgent public health issue at a global scale with potential consequences for quality of life and health of employees, especially in vulnerable groups such as migrants. The primary aim of this systematic review is thus to analyze and summarize existing research on the association between precarious employment and migrant workers’ mental health. Methods We will search PubMed/MEDLINE, PsycINFO, Web of Science (from January 1970 onwards) for original articles on observational studies (e.g., cohort, case-control and cross-sectional, and qualitative) published in English, German, Turkish, and Spanish. The primary outcome will be depression and anxiety disorders. Secondary outcomes will be burnout, sleeping problems, and occupational stress. Two reviewers will independently screen all citations, full-text articles, and abstract data. Potential conflicts will be resolved through discussion. The methodological quality (or risk of bias) of individual studies will be appraised using an appropriate tool. A narrative synthesis will summarize and explain the characteristics and findings of the studies. If feasible, we will conduct random effects meta-analyses where appropriate. Discussion This systematic review will analyze the ways in which precarious employment affects migrant workers’ mental health and the process that underlies this relationship. The results from the systematic review outlined in this protocol will be of interest to labor and health professionals, policy makers, labor unions, and non-governmental organizations. Our findings may encourage and impel related policy makers to establish human-focused, safe and healthy work environments, and workplace conditions. Systematic review registration PROSPERO, CRD42019132560